2023
DOI: 10.1007/s10531-023-02591-1
|View full text |Cite
|
Sign up to set email alerts
|

Harmonizing multi-stakeholder interests to improve forest conservation in Southern Kenya

Abstract: The cloud forests of the Taita Hills are valuable refuges for numerous endemic and rare animal and plant species. They also provide various ecosystem services that support subsistence farming. Due to the large-scale destruction and conversion of these species-rich natural forests into subsistence agriculture and plantations of exotic tree species, most of the natural cloud forest habitats have disappeared and ecosystem services have been significantly diminished. Despite numerous conservation initiatives, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Other studies have shown that disruptions not only change species composition and structure but can result in the extinction of sensitive species altering ecosystem functionality (Elijah et al, 2015.;Pellikka et al, 2013). Over-harvesting, deforestation, and replacement by non-native plants have further exacerbated these impacts affecting animal species composition and ecosystem functions (Medley et al, 2017;Watuma et al, 2022;Habel et al, 2023). Based on this study, the following research questions were addressed; How does the abundance of pollinators vary in the three ecosystem types?…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies have shown that disruptions not only change species composition and structure but can result in the extinction of sensitive species altering ecosystem functionality (Elijah et al, 2015.;Pellikka et al, 2013). Over-harvesting, deforestation, and replacement by non-native plants have further exacerbated these impacts affecting animal species composition and ecosystem functions (Medley et al, 2017;Watuma et al, 2022;Habel et al, 2023). Based on this study, the following research questions were addressed; How does the abundance of pollinators vary in the three ecosystem types?…”
Section: Introductionmentioning
confidence: 95%
“…The indigenous cloud forests in the Taita Hills have been decreasing signi cantly over the past 200 years due to extreme demographic pressure, high rates of poverty, and deforestation (Hohenthal et al, 2015). The forest covers a variety of vegetation structures, ranging from herbs to trees that provide different ecological services (Habel et al, 2023). The Taita locals conduct and rely on subsistence agriculture thus making the pristine forests and landscapes essential for providing the services needed to support human well-being (Habel & Ulrich, 2021),…”
Section: Description Of the Study Areamentioning
confidence: 99%